Impacts of Climate Change and Anthropogenic Stressors on Marine Ecosystems: A Comparative Study of Coral Reefs, Kelp Forests, and Arctic Fjords - David Sunday Araoti* (International Journal of Marine Life, 2026)
The accelerating impacts of climate change and human activities are profoundly reshaping marine ecosystems, threatening biodiversity, and altering trophic dynamics. This study synthesizes recent research on the responses of marine flora and fauna to temperature fluctuations, ocean acidification, pollution, and overfishing, highlighting the cascading effects on primary production, nutrient cycling, and ecosystem resilience. Using a combination of field surveys, remote sensing data, and meta-analytical approaches, we quantified biodiversity shifts across multiple marine habitats, from coral reefs to pelagic zones. Our findings reveal significant declines in key vertebrate and invertebrate populations, coupled with changes in species composition and trophic interactions. Furthermore, we identify critical hotspots for conservation and propose integrated management strategies that balance human use with ecosystem sustainability. This work provides actionable insights for marine policymakers, conservation practitioners, and relevant stakeholders by offering a comprehensive understanding of the challenges posed by ongoing environmental stressors. It highlights the critical need for evidence-based and adaptive management strategies to effectively address the accelerating loss of marine biodiversity. Furthermore, the study emphasizes the importance of integrating scientific research with policy frameworks to enhance conservation outcomes and ensure sustainable utilization of marine resources. By identifying key drivers of ecosystem degradation and proposing practical mitigation approaches, this work supports informed decision-making processes aimed at preserving ecosystem functionality, maintaining ecological balance, and safeguarding marine life for future generations in the face of climate change and anthropogenic pressures.
Keywords: Climate change; Keywords: Marine biodiversity; Marine conservation; anthropogenic impacts; ecosystem processes; trophic dynamics